The falklands war 1982 - Anderson, Duncan ([S.l.] : Osprey Publishing, 2002)
The Argentine invasion of the Falklands in 1982 sparked national outrage and Britain felt she had to avenge the humiliation and protect her own. This volume explores both the military and political dimensions of this important conflict, including detailed accounts of the air / sea battle, the Battle for San Carlos Water, Goose Green, Mt Harriet, Tumbledown and many others. It explains how success in the Falklands set the stage for the years of Thatcher's dominance, and restored British prestige. Including first hand accounts from both soldiers and civilians, this is an interesting and thoroughly up to date appraisal.